Biotechnological mechanism for improving plant remobilization of phosphorus during leaf senescence. Issue 2 (27th August 2019) - Da Ros, Letitia M.; Mansfield, Shawn D.
Summary: Phosphorus enrichment of aquatic ecosystems through diffuse source pollution is an ongoing issue worldwide. A potential solution lies in the use of fast‐growing, multipurpose feedstocks, such as trees, to limit the flow of phosphorus into riparian areas through luxury consumption. However, the perennial nature of trees and their use of leaves as storage organs for excess phosphorus may reduce the effectiveness of contaminant removal during periods of leaf abscission. In an attempt to improve phosphorus remobilization during autumnal senescence, transgenic hybrid poplar P39 ( Populus alba × Populus grandidentata ) and Arabidopsis thaliana harbouring a constitutively expressed low‐affinity potato phosphate transporter (35S::StPht1‐1) were generated using Agrobacterium ‐mediated transformation. For both species, the highest expressing 35S::StPht1‐1 lines were grown alongside wild‐type plants and subjected to increasing phosphate applications. StPht1‐1 expression in A. thaliana led to a reduction in biomass when grown under high‐phosphate conditions and had no effect on phosphate remobilization during senescence. In contrast, StPht1‐1 constitutive expression in P39 resulted in increased leaf phosphate content in the highest expressing transgenic line and minimal to no effect on P resorption efficiency. Surprisingly, sulphate resorption showed the greatest improvement in all three transgenic poplar lines, displaying a 31%–37% increase in resorption efficiency. These results highlight the complexity of nutrient resorption mechanisms in plants.